2011
DOI: 10.21273/jashs.136.6.429
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Free Amino Acid Content in ‘Jonagold’ Apple Fruit as Related to Branched-chain Ester Production, Ripening, and Senescence

Abstract: The relationship among the free amino acid content, the expression of genes related to branched-chain amino acid metabolism {branched-chain aminotransferase [BCAT], α-keto acid decarboxylase [pyruvate decarboxylase (PDC)], and threonine deaminase [TD]}, and the production of branched-chain (BC) esters during ripening and senescence in ‘Jonagold’ apple fruit (Malus ×domestica) was studied. Eighteen amino acids were measured by liquid chromatography coupled with tandem mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 76 publications
6
54
0
Order By: Relevance
“…E). The accumulation of isoleucine in the control apples is in agreement with previous reports (Magné et al , Defilippi et al , Sugimoto et al ). Valine accumulated significantly in the 1‐MCP treated but not in the control apples (Fig.…”
Section: Resultssupporting
confidence: 93%
“…E). The accumulation of isoleucine in the control apples is in agreement with previous reports (Magné et al , Defilippi et al , Sugimoto et al ). Valine accumulated significantly in the 1‐MCP treated but not in the control apples (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Tissue‐specific expression analysis revealed that PDC1 was expressed at a higher level in reproductive tissues compared with vegetative tissues, with an induction of expression in ripe fruit (Figure a), suggesting a role in ripening‐associated processes. PDCs identified in other fruits such as strawberry and apple also exhibit a ripening‐related expression pattern (Aharoni et al ., ; Moyano et al ., ; Sugimoto et al ., ). By contrast, PDC2 expression was low in fruit and highest in anther, pistil, ovary and root tissues (Figure b).…”
Section: Discussionmentioning
confidence: 97%
“…The general metabolic route for BCAA‐derived volatile formation in plants was thought to proceed in a similar way as that in bacteria or yeast, where BCAAs undergo an initial transamination leading to the formation of the corresponding branched‐chain α‐ketoacid, and decarboxylation followed by reduction and esterification giving rise to branched‐chain aldehydes, alcohols and esters, respectively (Hazelwood et al ., ). However, recent investigations in tomato fruit suggest that branched‐chain α–ketoacids, rather than BCAAs are the precursors of branched‐chain volatiles (Sugimoto et al ., ; Kochevenko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The important function of citramalic acid has been reported and realized in plant. It participates in the tricarboxylic acid (TCA) cycle (Sugimoto et al, 2011), and is highly suitable for using as a ligand in coordination chemistry (Aakeroy et al, 2015). Moreover, citramalic acid is involved in the branched-chain amino acid biosynthesis pathway (Leroy et al, 2015) and is expected to act as an acid catalyst for the transesterification reaction (Ilham & Saka, 2009).…”
Section: Introductionmentioning
confidence: 99%